Clinical Profile and Management of Chronic Pancreatitis in Tertiary Care Centre - Amey Gawali; Nitin Wasnik; MS; Satish Deshmukh (Pancreas, 2025)
BackgroundConstant inflammation and irreversible pancreatic tissue destruction are hallmarks of the disease of chronic pancreatitis (CP), which results in the decrease of both exocrine and endocrine function over time. It is a multifactorial disease, with a wide range of symptoms and geographic variation. AimAim of this study is to study clinical profile and management of CP with respect to demography, clinical findings, lab parameters, imaging investigations and management modalities.MethodsA cross-sectional observational study was conducted which included the patients admitted to the tertiary care center presenting with the clinical diagnosis of CP. The study was conducted over a period of 2-years from November 2019 to October 2021. A total sample size of 71 patients was included.ResultsIn the study, it was observed that the majority of patients were in the age group of 51-60-years (47.89%) followed by 41-50-years (21.12%) mean age ranges from 56.54±12.63-years. The majority of patients were male (76.06%) and females were 23.94%. The distribution of patients according to aetiology showed that the majority of patients had aetiology of alcoholism (43.66%) fol-lowed by idiopathic (29.57%) Gall/Biliary stones (21.12%) and post-operative (5.63%). Majority of patients presented with pain in the abdomen (85.92%). The distribution of patients according to ultrasound sonography test (USG) findings showed that majority of patients shows pancreatic calcification (54.93%) followed by pancreatic pseudocyst (32.39%) and gall stones (19.72%). The distribution of patients according to computed tomography (CT) findings showed that majority of patients shows pancreatic cal-cification (70.42%). In the present study, it was observed that majority of patients were managed conservatively (43.66%) followed by cystogastrostomy (18.31%) and cystojejunostomy (8.45%). Endoscopic retrograde cholangiopancreatography (ERCP) was done among 14 (19.72%) patients. Lateral pancreaticojejunostomy was done in 6 (8.45%) patients and pancreaticoduodenectomy (Classical Whipple’s) was done in 4 patients (5.63%). The distribution of patients according to pain relief by various management showed that majority of getting relief from pain by surgery (69.23%) followed by ERCP (35.71%) and the least by conservative/analgesics (6.45%). ConclusionChronic pancreatitis is progressive inflammatory disease. Alcoholic pancreatitis being most common etiology. Pain is most com-mon presenting symptom. CT scan abdomen most useful in confirming diagnosis in our set up. Pseudocyst being common com-plication seen. Surgery gives relief of pain in most of the cases. The key to a better outcome is making the right decisions in terms of diagnosis, patient selection for surgery, and surgical type.